Ecological and socio-cultural potential of human modified forest landscapes in conservation of tree species diversity : the case of Vhembe biosphere reserve, South Africa - Chirwa, Paxie W. (University of Pretoria, 2022)
Thesis (PhD (Forest Science))--University of Pretoria, 2019.